Meningkatkan kualitas hidup sehat masyarakat Dayak melalui lokakarya Sekolah Sehat di Kabupaten Landak Kalimantan Barat - Rizki Hegia Sampurna (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The Indonesian government continues to strive to implement the health promoting school program nationwidely. Yet the disparity in its implementation is still high. Most schools in remote areas have not been able to implement it. Such as Sekolah Dasar Negeri 08 Berinang Mayun and Sekolah Dasar Negeri 02 Sidan which are located in the middle of palm oil plantations in Landak, West Kalimantan. Students of and communities around the two schools are Dayak people whose health quality are still poor. Based on that, we conducted a health-promoting school workshop at the two schools. The workshop was carried through lectures, focus group discussions, and simulations. In the end, the participants were required to produce a health promoting school plan as an outcome. A number of indicators such as KWL analysis, participants’ feedback and pre-post test analysis showed that there is an increase in the knowledge and skills of participants regarding the health promoting school program. But the most obvious achievement is that participants have designed a health-promoting school plan that they will carry out in their respective schools.